PENGARUH KUALITAS PRODUK, CITRA MEREK DAN KENYAMANAN TERHADAP MINAT BELI ULANG KONSUMEN PADA MASKER SENSI DISAAT PANDEMI COVID-19 - Yayuk Sundari; Yulius Setiadi ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2022)
At the end of 2019, the emergence of Corona Virus Disease or Covid -19 in China (Wuhan) and entering Indonesia in March 2020. This virus attacks the respiratory tract in humans which ultimately requires people to wear masks to prevent transmission of COVID-19. This makes people always buy masks to prevent transmission of the virus, namely sensi masks because these masks are surgical masks. In choosing masks for repurchase intention, several factors are considered by consumers, including product quality, brand image, and comfort. Muhammadiyah University of Bengkulu. The population in this study were students of the Management Study Program, Muhammadiyah University of Bengkulu. The use of sensi masks in Bengkulu City. The data collection method was using a questionnaire. Sampling using purposive sampling method with a total of 180 respondents. Testing the instrument using validity and reliability tests. The data analysis technique to answer the hypothesis in this study used multiple linear regression analysis. The results showed that Product Quality (X1) had a positive and significant effect on repurchase interest (Y) on sensi masks during the covid-19 pandemic in University Management Study Program students. Muhammadiyah Bengkulu. Brand Image (X2) has a positive and significant influence on repurchase interest (Y) on sensi masks during the covid-19 pandemic among students of the Management Study Program at Muhammadiyah University of Bengkulu. Convenience (X3) has a positive and significant effect on repurchase interest (Y) on sensi masks during the covid-19 pandemic among students of the Management Study Program at Muhammadiyah University of Bengkulu. Keywords: Product Quality, Brand Image, Convenience, and Repurchase Interest